Climate Change Education within Canada’s Regional Curricula: A Systematic Review of Gaps and Opportunities - Field, Ellen; Spiropoulos, Gia; Nguyen, Anh Thu; Grewal, Rupinder K. (Canadian Journal of Educational Administration and Policy / Revue canadienne en administration et politique de l’éducation, 2023)
This paper reports on curriculum analysis of climate change expectations in Canada’s provincial curricula. The research is focused on curriculum policy in Canadian provinces; however, it pertains to an international audience as Article 12 of the Paris Agreement, the international treaty on climate mitigation, adaptation and finance, calls for signatories to “enhance climate change education,” and the United Nations Educational, Scientific and Cultural Organization (UNESCO) have called for environmental education to be a core curriculum component by 2025, which will require all countries to evaluate and improve their curricula globally. Curriculum policy within Canada has not yet been aligned with these policy calls, and our analysis showed fractured and uneven inclusion of climate change. Data findings present explicit climate change education curriculum expectations for each province according to grade, subject, and mandatory versus elective courses. The review shows uneven inclusion of climate change topics, themes, and units within grade 7 – 12 curricula, with most expectations occurring in elective senior secondary courses. A second level of analysis with a ranking tool indicates shallow inclusion. The paper concludes with recommendations for addressing gaps.